2018
DOI: 10.3390/cancers10070232
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Strategies to Allogeneic Transplant for Older AML Patients

Abstract: Treatment options for older patients with intermediate or high-risk acute myeloid leukemia (AML) remain unsatisfactory. Allogeneic stem cell transplantation, the treatment of choice for the majority of younger AML patients, has been hampered in elderly patients by higher treatment related mortality, comorbidities and lack of a suitable donor. With the higher availability of suitable donors as well as of reduced intensity conditioning regimens, novel low intensity treatments prior to transplantation and optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
(123 reference statements)
2
3
0
Order By: Relevance
“…A study by the European Blood and Marrow Transplantation (EBMT) group showed cumulative incidence of relapse after allo-SCT 32% ± 1% among AML patients and the longer intervals from transplant to relapse, low bone marrow tumor burden at relapse, and the absence of aGVHD were identified as prognostic factors associated with survival improvement in these patients 52 . Similar to prior reports we observed poor survival following AML relapse after allo-SCT 49 , 53 . OS had a strong relationship with leukemia recurrence (P<0.001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study by the European Blood and Marrow Transplantation (EBMT) group showed cumulative incidence of relapse after allo-SCT 32% ± 1% among AML patients and the longer intervals from transplant to relapse, low bone marrow tumor burden at relapse, and the absence of aGVHD were identified as prognostic factors associated with survival improvement in these patients 52 . Similar to prior reports we observed poor survival following AML relapse after allo-SCT 49 , 53 . OS had a strong relationship with leukemia recurrence (P<0.001).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, 97% of patients were age <40 years at the time of allo-SCT. No significant relationship between age at transplant time and survival was detected (P=0.73) in the study, It might be due to overall young age of study group which is consistent with the similar study by Shokouhi et al on 587 AML patients with a mean age of 27.27 ± 12.45 years at transplant time 49 . Most studies have shown that people over the age of 60 years are less likely to survive than younger people 50 , 51 .…”
Section: Discussionsupporting
confidence: 89%
“…The role of HMAs is well-established in the frontline treatment of older patients with AML, including bridging to transplant [29], while no randomized trials have been performed in refractory or relapsed disease. In the absence of prospective studies, different retrospective observations have demonstrated the potential utility of either AZA or DAC.…”
Section: Intensive Salvage Chemotherapy and Hypomethylating Agentsmentioning
confidence: 99%
“…In AML, they are primarily a treatment option for patients not eligible for intensive induction. They can also be used as bridging to HCT in selected subgroups of patients [117,118], and can potentially have a place as maintenance treatment after remission in elderly patients ineligible for HCT [119]. Treatment with HMAs in patients with s-AML is an appealing option due of the overrepresentation of typical adverse risk aberrations such as complex or monosomal karyotypes, abnormalities in chromosome 5, 7 and 17, and TP53 mutations that might predict response to HMAs [6,120,121].…”
Section: Hypomethylating Agentsmentioning
confidence: 99%